SHARING THE READING SECRET: USING THINK-ALOUD TO IMPROVE READING COMPREHENSION OF L2 TEXTS - Barjesteh, Hamed (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
This study investigates the effects of thinking-aloud on L2 reading in relation with the type of task Iranian EFL readers engage in while reading activity. In so doing, 360 students were selected and assigned to experimental and comparison groups. The subjects in experimental groups were instructed to verbalize whatever they were thinking as their thought naturally came to mind while reading and doing the assigned tasks. The results indicated that the instructional procedure had contributed to the improvement of the EFL students’ reading comprehension. By and large, the analysis of think-aloud protocol can provide language learners with a means for monitoring their reading process. Moreover, it gives an opportunity for language teachers to become more sensitized to various comprehension problems that students encounter and offers clues to understand potential weakness that students may have in their L2 reading.